Behavioral Analysis on IPv4 Malware in both IPv4 and IPv6 Network Environment - M., Zulkiflee; Abdollah, M. F.; Othman, M. F. I.; Abu, Nur Azman; Sahib, S. (2011)
Malware is become an epidemic in computer net-work nowadays. Malware attacks are a significant threat to networks. A conducted survey shows malware attacks may result a huge financial impact. This scenario has become worse when users are migrating to a new environment which is Internet Protocol Version 6. In this paper, a real Nimda worm was released on to further understand the worm beha-vior in real network traffic. A controlled environment of both IPv4 and IPv6 network were deployed as a testbed for this study. The result between these two scenarios will be analyzed and discussed further in term of the worm behavior. The ex-periment result shows that even IPv4 malware still can infect the IPv6 network environment without any modification. New detection techniques need to be proposed to remedy this prob-lem swiftly.